2020
DOI: 10.1177/0030222820966934
|View full text |Cite
|
Sign up to set email alerts
|

Age Changes and Suicidal Activity in Iran Over the Past Decade: A Systematic Review and Meta-Analysis

Abstract: This review study fills an important gap by aiming to determine the age changes in attempted and completed suicide in Iran during the past decade. A systematic review of related articles in international and Iranian databases from January 2008 to January 2020 was first conducted and relevant studies were extracted based on established criteria. Results showed that the mean age of suicide in Iran is 29.8 (range 27.7 – 31.8) years old for men and 27.4 (range 25.8 – 28.9) for women (P < 0.0001). The youngest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…For example, research has previously identified individuals under 30 as the main group affected by complete suicide in Iran. 3 Interestingly, the results of the mentioned study are closely similar to the findings of these earlier investigations. However, Mirahmadizadeh et al specify the self-immolation cases as exclusion criteria.…”
supporting
confidence: 90%
“…For example, research has previously identified individuals under 30 as the main group affected by complete suicide in Iran. 3 Interestingly, the results of the mentioned study are closely similar to the findings of these earlier investigations. However, Mirahmadizadeh et al specify the self-immolation cases as exclusion criteria.…”
supporting
confidence: 90%
“…An earlier and recent systematic review from January 2008 to January 2018 showed that the mean age of suicide in Iran was 29.8 years (age range: 27.7-31.8 years) for men and 27.4 years (age range: 25.8-28.9 years) for women. 30 These findings demonstrate that suicide among Iranian women occurred at younger ages than men over the past decade. 15 , 30 However, identifying the exact causes of this heterogeneity is beyond this paper’s scope, and further research is warranted.…”
Section: Discussionmentioning
confidence: 78%
“… 30 These findings demonstrate that suicide among Iranian women occurred at younger ages than men over the past decade. 15 , 30 However, identifying the exact causes of this heterogeneity is beyond this paper’s scope, and further research is warranted. On the other hand, the age range reported was significantly lower than that in our findings (34 years).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This finding underscores the importance of assessing eating disorders, especially in younger diabetic patients, to prevent morbidities. This result could be because of that younger Iranian people were more at the risk of suicide (29.8 for men and 27.4 for women as meta-analysis of Sharif Nia et al discussed (16).…”
Section: Discussionmentioning
confidence: 99%